Analisis Penerapan Sistem Informasi Manajemen Daerah (SIMDA) Keuangan Pada Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Lombok Barat - Ramayanto, Ramayanto; Reinelda Tri Yunarni, Baiq (Lembaga Penelitian dan Pendidikan Mandala, 2022)
SIMDA Finance is an application program used to assist local governments in the field of financial management. The purpose of implementing a financial SIMDA is to produce financial reports and financial information in a timely, complete, accurate, and reliable manner in accordance with applicable regulations and to encourage the realization of Good Governance and the implementation of regional financial management based on information technology. This study aims to obtain an overview of the implementation of the Regional Management Information System (SIMDA) of Finance at the Regional Development Planning Agency (BAPPEDA) of West Lombok Regency.The research method used is a qualitative method with a phenomenological approach. The results of this study indicate that in general, employees at BAPPEDA Lombok Barat already know the meaning of financial SIMDA, seen from their understanding of the meaning, benefits and objectives as well as the required inputs and outputs generated from the processing. Supporting factors that are owned by BAPPEDA West Lombok in the optimal implementation of SIMDA Finance, among others: Active communication or socialization regarding the purpose of implementing or benefiting from the application of the system. Human Resources who are reliable/compliance both in number and capacity There is an attitude of the implementor who accepts/agrees with the implementation of the implementation of SIMDA Finance as well as support from the head of the office/leader.